Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1210/endo.134.6.8194490
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and in situ localization of murine endoglin reveal that it is a transforming growth factor-beta binding protein of endothelial and stromal cells.

Abstract: Endoglin is an integral membrane glycoprotein predominantly expressed on human endothelial cells and recently shown to bind transforming growth factor-beta 1 (TGF beta 1) with high affinity. We now report the cloning and sequencing of a full-length murine endoglin complementary DNA of 2902 base pairs which hybridizes specifically with a single messenger RNA (mRNA) species. The polypeptide of 653 amino acids has an overall identity of 72% with human and porcine endoglin. The transmembrane and cytoplasmic domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
2

Year Published

1998
1998
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 0 publications
3
50
0
2
Order By: Relevance
“…This species with respect to humans shows an apparently higher expression of the antigen in normal organs. 14,43 Endoglin-specific MAbs, radiolabeled or conjugated with Ricin A chain, have already been used in tumor therapy animal models, with a strong antitumor efficacy without side effects being observed. 29,30,44 Since the MAb used is specific for human endoglin and gives a weaker reaction with mouse endoglin, the authors suggested that an even stronger antitumor effect can be expected in therapeutic applications on humans, however, a higher risk of side effects on normal tissues should also be taken into account.…”
Section: Analysis Of Endoglin Expression In Neoplastic and Normal Hummentioning
confidence: 99%
See 1 more Smart Citation
“…This species with respect to humans shows an apparently higher expression of the antigen in normal organs. 14,43 Endoglin-specific MAbs, radiolabeled or conjugated with Ricin A chain, have already been used in tumor therapy animal models, with a strong antitumor efficacy without side effects being observed. 29,30,44 Since the MAb used is specific for human endoglin and gives a weaker reaction with mouse endoglin, the authors suggested that an even stronger antitumor effect can be expected in therapeutic applications on humans, however, a higher risk of side effects on normal tissues should also be taken into account.…”
Section: Analysis Of Endoglin Expression In Neoplastic and Normal Hummentioning
confidence: 99%
“…11 It is transiently expressed as well during human heart development. 12,13 Recently, high expression in intestine, stomach and uterine stromal cells in mouse has been reported, 14,15 and an MAb raised against human mesenchymal stem cells has been shown to recognize an epitope on endoglin. 16 Two different isoforms have been identified, a full-length protein with a cytoplasmic domain of 47 amino acids, 17 and a splice variant with a truncated cytoplasmic tail of 14 amino acids.…”
mentioning
confidence: 99%
“…To test this possibility, we used the mouse fibroblast cell line NCTC, which expresses murine endoglin [7]. The existence of interspecies dimers between human and murine transmembrane endoglins could be demonstrated by using non-cross-reactive mAb against murine or human endoglin ( Figure 6A).…”
Section: Effect Of Soluble Forms Of Endoglin On the Expression Of Tramentioning
confidence: 99%
“…HHT is a highly penetrant autosomal dominant vascular dysplasia associated with frequent epistaxis, gastrointestinal bleeding, telangiectases and arteriovenous malformations in brain, lung and liver [3,4]. Endoglin (CD105) is a 180 kDa homodimeric membrane glycoprotein strongly expressed by human endothelial cells [5] ; it is also present in syncytiotrophoblasts of full-term placenta [6], stromal cells [7,8] and certain haemopoietic cells [9][10][11][12]. Two different isoforms, Lendoglin and S-endoglin, differing in the amino acid compositions of their cytoplasmic tails, have been characterized [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Endoglin plays an important role in mammalian physiology as demonstrated by genetic inactivation, since Endoglin null (Eng À/À ) murine embryos die of vascular defects at 10-10.5 days post coitum (Bourdeau et al, 1999;Li et al, 1999;Arthur et al, 2000). Endoglin is a disulfide-linked homodimer of 180 kDa expressed in endothelial cells (Gougos and Letarte, 1988Letarte, , 1990Li et al, 2000), macrophages (Lastres et al, 1992), stromal cells (St-Jacques et al, 1994;Robledo et al, 1996), and other cellular lineages within the vascular system and connective tissues (Fonsatti et al, 2001). Several tumor cells also express endoglin, including pre-B-cell and monocytic leukemia (Quackenbush and Letarte, 1985;Haruta and Seon, 1986;Lastres et al, 1992;Zhang et al, 1996), melanoma (Altomonte et al, 1996), choriocarcinoma (Letamendia et al, 1998b), and ovarian carcinoma (Jindal et al, 1995).…”
Section: Introductionmentioning
confidence: 99%